2006
DOI: 10.1093/eurheartj/ehi844
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine test in the diagnosis of unexplained syncope: marker of conducting tissue disease or neurally mediated syncope?

Abstract: Adenosine test (supine administration of a 20 mg intravenous bolus with electrocardiographic and blood pressure monitoring) has been endorsed by the European Society of Cardiology guidelines on syncope management as an 'experimental' test in the diagnosis of unexplained syncope. The test is quick and cheap, but there is no consensus as to what condition, if any, the adenosine test is exposing, with conducting tissue disease and neurally mediated syncope proposed by various authors. In this article, we review t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 27 publications
0
4
0
2
Order By: Relevance
“…Thus, the negative chronotropic and dromotropic actions of ATP are mediated by adenosine and the vagus nerve (Pelleg et al 1997); a mechanism found in cat, dog and man, but not in rodents (Pelleg et al 1990b). Brignole et al (Brignole et al 2003) and Flammang et al (2006) used bolus intravenous injections of ATP as a diagnostic tool in patients with syncope of unknown cause (for references, see Parry et al 2006). The former group has used a maximal RR interval > 6 s while the latter group has used complete AVN block duration > 10 s as an indication of a positive test.…”
Section: Cardiac Electrophysiology Of Adenosine: Recent Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the negative chronotropic and dromotropic actions of ATP are mediated by adenosine and the vagus nerve (Pelleg et al 1997); a mechanism found in cat, dog and man, but not in rodents (Pelleg et al 1990b). Brignole et al (Brignole et al 2003) and Flammang et al (2006) used bolus intravenous injections of ATP as a diagnostic tool in patients with syncope of unknown cause (for references, see Parry et al 2006). The former group has used a maximal RR interval > 6 s while the latter group has used complete AVN block duration > 10 s as an indication of a positive test.…”
Section: Cardiac Electrophysiology Of Adenosine: Recent Developmentsmentioning
confidence: 99%
“…In view of the fact the both ATP and adenosine suppress ventricular escape rhythms (Lerman et al 1988; Pelleg et al 1986), it is difficult to interpret the RR interval data as the rate of ATP degradation, and hemodynamic factors can directly affect this parameter. Using the RR interval > 10 s criterion, it seems that ATP can identify a cohort of elderly patients in whom the mechanism of syncope is bradycardia and who may benefit from pacemaker therapy (see Flammang and AMS Investigators 2006; Flammang et al 2005; Parry et al 2006). In these patients, the bradycardia can be due to SN dysfunction, AVN dysfunction, abnormal vagal input to the heart, and any combination of these three causes.…”
Section: Cardiac Electrophysiology Of Adenosine: Recent Developmentsmentioning
confidence: 99%
“…38 However, managing the older patient with less clear-cut syncopal disease requires a broad knowledge base across multiple body systems and of multiple chronic conditions, a solid grounding in clinical pharmacology, and appreciation of the vagaries of presentation. In the neurally mediated disorders, the evidence base in relation to the older patient is even less clear-cut, with randomized controlled trials related to the management of the older syncopal patient being limited to pacing intervention studies in patients with a positive adenosine test, 39,40 CSS associated with unexplained falls, [41][42][43] and VVS. 19,44 The remainder of this article uses real-life clinical vignettes to describe, explain, and offer practical hints and tips in each of these areas.…”
Section: Managing Syncope In the Older Patient: A Case-based Approachmentioning
confidence: 99%
“…The administration of either a 20 mg bolus of adenosine intravenously, or by continuous infusion during tilt table testing has been suggested in the diagnosis of syncope in the last decade [50]. However there is considerable confusion regarding the putative underlying diagnosis uncovered by a "positive" test, with the most likely being bradyarrhythmia pacing indications [51].…”
Section: Adenosine Testingmentioning
confidence: 99%